Efficacy and safety of bismuth quadruple regimens containing minocycline and vonoprazan for eradication of Helicobacter pylori: Real‐world evidence - Qiyunna He; Yan Ou; Huili Zhu; Zhiqian Chen; Dailan Yang; Qian Cheng; Xia Yin; Lina Xiao; Lin Cai; Yan Ye; Xin Xu; Juan Liao (JGH Open, 2024)
Abstract Background and Aim To evaluate the efficacy and safety of minocycline, vonoprazan, amoxicillin, and bismuth quadruple therapy for Helicobacter pylori (H. pylori) treatment. Methods From August 2022 to May 2023, clinical data were collected from patients who received H. pylori eradication treatment at West China Fourth Hospital, Sichuan University. One group received the MVAB regimen (amoxicillin, minocycline, vonoprazan, and colloidal bismuth pectin), while another group received the FOAB regimen (amoxicillin, furazolidone, omeprazole, and colloidal bismuth pectin), both administered for 14 days. Follow‐up assessments of safety and compliance were conducted within 1 week after treatment completion. One and a half months after treatment, the success of eradication was evaluated using the urea breath test. Results For the MVAB regimen as a first‐line treatment, the eradication rate was 90.1% (127/141, 95% CI: 85.1–95.1%) in the ITT analysis and 93.4% (127/136, 95% CI: 89.2–97.6%) in the PP analysis as a first‐line treatment. As a second‐line treatment, the eradication rate was 91.3% (21/23, 95% CI: 78.8–103.8%) in both analyses. For the FOAB regimen as a first‐line treatment, the eradication rate was 98.0% (50/51, 95% CI: 94.1–101.2%) in the ITT analysis and 100% (50/50, 95% CI: 100%) in the PP analysis. As a second‐line treatment, the eradication rate was 100% (6/6, 95% CI: 100%) in both analyses. Moreover, there was no significant difference in the incidence of adverse events between the two groups (MVAB regimen: 5.5% and FOAB regimen: 8.8%; P > 0.05). Conclusions The MVAB regimen could indeed be a viable alternative treatment option to conventional therapies.